THE POTENTIAL UTILIZATION OF TIKTOK AS DIGITAL MEDIA IN ARABIC LANGUAGE LEARNING - Mustafiqul Hilmi; Vikria Tahta Alvina; R. Taufiqurrochman (Kitaba, 2024)
This research aims to explore the potential for using TikTok as a digital media in Arabic language learning, focusing on identifying the utilization of TikTok in Arabic language learning. This research was conducted in response to the increasing use of technology using digital media in education, especially using TikTok as media in Arabic language learning. The research method used is a literature study with a desk research approach, namely exploring data from empirical and relevant research. The research results show that TikTok is one of the social media platforms that can potentially be utilized for learning. TikTok, which is audio-visual based, is seen as attractive by students. In addition, many features can be used to increase students' creativity. As a learning media, TikTok also can make it easier for educators to deliver learning materials effectively. The characteristics of TikTok are also easy to use and are close to students' personalities because they are used in their daily lives. The utilization of TikTok in Arabic language learning can be applied to improve the four Arabic language skills by utilizing the available features. For example, in learning listening (istima') skills using the For Your Page (FYP) feature or the Hashtag feature to search for Arabic content, in speaking skills (kalam) through the voice recording feature, reading skills (qira'ah) through the duet feature, writing skills (kitabah) using the edit and write features.